Mechanistic and kinetic insights into the ligand-promoted depassivation of bimetallic zero-valent iron nanoparticles. Issue 4 (21st June 2016) - He, Di; Ma, Xiaoming; Jones, Adele M.; Ho, Lam; Waite, T. David
Abstract : Little attention has been given to either the thermodynamics and kinetics of palladium-doped nanoscale zero-valent iron particles (Pd-nZVI) depassivation process or the effect of the presence of co-existent cations using ligand-assisted performance improvement strategies. Abstract : The effectiveness of using ligand-assisted strategies to improve the performance of palladium-doped nanoscale zero-valent iron particles (Pd-nZVI) towards contaminant removal has been investigated previously, however, little attention has been given to either the thermodynamics and kinetics of the Pd-nZVI depassivation process or the effect of the presence of co-existent cations. Results of laboratory investigations using EDTA as the ligand of choice indicate that the presence of Ca(ii ) and Mg(ii ) ions can significantly improve the ligand-promoted dechlorination efficiency of polychlorinated biphenyls (PCB) with the effect of divalent cations on PCB removal being more significant at higher concentrations of EDTA. The improvement in particle reactivity in the presence of Ca(ii ) and Mg(ii ) could be attributed to moderate elimination of outer Fe oxide layers induced by the relatively slow release of free EDTA from Ca and Mg–EDTA complexes. The slow release of free EDTA prevented excessive initial loss of Fe oxide surface sites required for PCB sequestration and ensured that sufficient EDTA remained available for the later-time removal of Fe oxide layers that were continuously formed as Fe 0 was oxidized. A mechanistically-based kinetic model for the ligand-promoted dissolution of Pd-nZVI has been developed with this model enabling quantitative understanding of the relatively complex interplay among Ca(ii ) and Mg(ii ) ions, EDTA and passivating Fe oxide layers during the contaminant degradation process.